Analisis Waktu dan Biaya dengan Metode Crash Duration pada Keterlambatan Proyek Pembangunan Jembatan Sei Hanyu Kabupaten Kapuas - Oetomo, Wateno; Priyoto, Priyoto; Uhad, Uhad (Media Ilmiah Teknik Sipil, 2017)
In analyzing the comparison of the cost of acceleration with the acceleration time used by the method Time Cost Trade Off. The analysis is done by using / shortening (crashing) time of implementation by using an alternative to increase working hours (overtime) for 3 hours. With apply the TCTO analysis, the implementation of the construction of the Sei Hanyu Bridge project after its duration performed calculations using the crash duration method, it was found that the time needed to accelerate the construction of the Sei Hanyu Bridge in Kapuas Regency for 1038 calendar days(148 weeks), can be accelerated 44 days from the original planning 1082 calendar days (155 weeks). With the acceleration of the completion of the construction of the Sei Hanyu bridge in Kapuas Regency, an additional fee of Rp. 175,160,710.43 is required with an additional cost (cost slope) of Rp 3,980,925.24 per day for 44 days, so the optimal costs needed to accelerate the construction of the Sei Hanyu bridge in Kapuas Regency was Rp. 45,102,729,928.11 originally planned for Rp.44,927,569,217.68